Mental Disorders and Intimate Partner Femicide: Clinical Characteristics in Perpetrators of Intimate Partner Femicide and Male-to-Male Homicide - Caman, Shilan; Sturup, Joakim; Howner, Katarina (Frontiers in Psychiatry, 2022)
Intimate partner violence against women is a global and persistent public health issue. An extreme manifestation of this problem is intimate partner femicide (IPF), the killing of a woman by a male partner. While declining trends of homicide rates have been observed over decades, rates of femicide and IPF have remained stable. Yet, IPF as a phenomenon has until recently been invisible in Europe, why research from the European countries on rates and characteristics of IPF has been relatively scarce. One area of research, particularly in need of further scrutiny, is to what degree perpetrators of IPF suffer from mental health conditions, and what the clinical features are. The objective of present study was to add to the existing literature by investigating prevalence and types of mental disorders in perpetrators of IPF, and to compare with male-to-male homicide (MMH) perpetrators. Our aim was also to examine life-time contact with psychiatric services, and, with missed opportunities in mind, contacts shortly preceding the homicide. With a retrospective design, this population-based study includes all solved cases of male-perpetrated homicides against intimate female partners (IPF) and other males (MMH) committed in Sweden between January 2007 and December 2009. Primary and secondary psychiatric diagnoses based on ICD, version 8, 9 or 10 from psychiatric inpatient as well as outpatient care have been retrieved. In order to identify mental disorders in perpetrators during commission of the homicidal offense, we also retrieved diagnoses from forensic psychiatric evaluations. Our results demonstrate that approximately one-third of the perpetrators, irrespective of homicide type, had been diagnosed with a mental disorder (excluding substance related disorders) at some point in life. Diagnosis of substance related disorders from psychiatric care was significantly more common in MMH perpetrators (37%) compared to IPF perpetrators (15%). Similarly low rates of major mental disorder were found in both groups (11%) when aggregating life-time diagnoses and diagnoses during commission of the crime. However, homicide-suicide in connection to the offense was relatively common in IPF perpetrators (20%). Thus, our study supports the notion that previous suicide attempts and suicide ideation are important indicators for predicting and possibly preventing IPF.